The Impact of the COVID-19 Epidemic on Orthodontic Patients in China: An Analysis of Posts on Weibo - Guo, Feiyang; Tang, Bojun; Qin, Danchen; Zhao, Tingting; Su, Yu-xiong; McGrath, Colman; Hua, Fang; He, Hong (Frontiers in Medicine, 2020)
Background: During the COVID-19 pandemic, many dental care services including orthodontic practice were suspended. Orthodontic patients turned to social media platforms to communicate, share experiences and look for solutions. Our study aimed to provide insights into the impact of the COVID-19 epidemic on orthodontic patients in China. Materials and Methods: Potentially eligible posts on Sina Weibo platform, the Chinese counterpart of Twitter, were collected between December 30, 2019 and April 18, 2020. Posts both related to orthodontics and COVID-19 were included, and then coded and classified by specific appliances and themes. Geographic and temporal distribution of the included posts were analyzed. In addition, time lagged cross correlation was performed to explore the association between the number of daily posts and daily new COVID-19 cases / deaths in China. Chi-square tests were employed to compare the differences between fixed appliances and aligners in problems / difficulties and feelings during the epidemic. Results: Of the 28,911 posts identified, 4484 were included in the analysis. The most frequently mentioned themes were appointments (n=2621, 58.5%), negative feelings (n=2189, 48.8%) and problems / difficulties (n=1155, 25.8%). The geographic and temporal distribution of posts were roughly consistent with the epidemiological data of COVID-19 in China. The number of daily posts was significantly associated with daily new COVID-19 cases / deaths in China (P < 0.05). Compared with clear aligners, patients with fixed appliances reported more problems / difficulties (P < 0.001) and negative feelings (P < 0.001), but fewer positive feelings (P < 0.001). Conclusions: Appointments were the greatest concern for orthodontic patients. Both treatment and psychological issues for orthodontic patients should be appropriately handled during the suspension of dental care services. Clear aligners were somewhat easier to manage than fixed appliances during COVID-19 epidemic.